The initial momentum of the system is,
![p_i=m_1u_1+m_2u_2](https://img.qammunity.org/2023/formulas/physics/college/1gmt8x4y25pwwrgu2qb14c5hmsw9pyvt36.png)
The final momentum of the system is,
![p_f=m_1v_1+m_2v_2](https://img.qammunity.org/2023/formulas/physics/college/8no0kualirzeb4zjjuvislutjgp9ko7tz5.png)
According to conservation of momentum,
![p_i=p_f](https://img.qammunity.org/2023/formulas/physics/college/e7rj8yeigkhgmt4s6ul64ny08zwwhw91ko.png)
Plug in the known expressions,
![\begin{gathered} m_1u_1+m_2u_2=m_1v_1+m_2v_2 \\ m_2v_2=m_1u_1+m_2u_2-m_1v_1 \\ v_2=(m_1u_1+m_2u_2-m_1v_1)/(m_2) \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/4vqic41s011xx7qevor32wj7nh8ui3koun.png)
Substitute the known values,
![\begin{gathered} v_2=\frac{(1381\text{ kg)(14.5 m/s)+(1381 kg)(13.4 m/s)-}(1381\text{ kg)(13.4 m/s)}}{1381\text{ kg}} \\ =\frac{(1381\text{ kg)(14.5 m/s)}}{1381\text{ kg}} \\ =14.5\text{ m/s} \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/1kef8edcwm00cuzguqzrhtg7cvev5wzasn.png)
The initial kinetic energy of the system is,
![K=(1)/(2)m_1u^2_1+(1)/(2)m_2u^2_2](https://img.qammunity.org/2023/formulas/physics/college/yf01xvbnyej4tjsrv10w1oo6qgsfxf3dup.png)
The final kinetic energy of the system is,
![K^(\prime)=(1)/(2)m_1v^2_1+(1)/(2)m_2v^2_2](https://img.qammunity.org/2023/formulas/physics/college/tcsivuzutvywwjbf8ys926tn9s51ni838l.png)
The change in kinetic energy of the system is,
![\Delta K=K^(\prime)-K](https://img.qammunity.org/2023/formulas/physics/college/ass7ljbspyplhk9bxh8diuxfgcbul9csx1.png)
Plug in the known expressions,
![\begin{gathered} \Delta K=(1)/(2)m_2v^2_2+(1)/(2)m_1v^2_1-((1)/(2)m_2u^2_2+(1)/(2)m_1u^2_1) \\ =(1)/(2)m_2(v^2_2-u^2_2)+(1)/(2)m_1(v^2_1-u^2_1) \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/r8vvgr1dqlwu17qtdvnyp8fxwb1w5qb551.png)
Substitute the known values,
![\begin{gathered} \Delta K=(1)/(2)(1381kg)((14.5m/s)^2-(13.4m/s)^2)- \\ (1)/(2)(1381kg)((13.4m/s)^2-(14.5m/s)^2) \\ =(690.5\text{ kg)(}210.25m^2s^(-2)-179.56\text{ }m^2s^(-2))-(690.5\text{ kg)(}179.56\text{ }m^2s^(-2)-210.25\text{ }m^2s^(-2)) \\ =(690.5\text{ kg)(}30.69\text{ }m^2s^(-2))(\frac{1\text{ J}}{1\text{ kg}m^2s^(-2)})-(690.5\text{ kg)(-30.69 }m^2s^(-2)) \\ =21191.4\text{ J+21191.4 J} \\ =42382.8\text{ J} \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/tpw2hyk9fpyjnaccxal09f7yso268tkcce.png)
Therefore, the change in kinetic energy of the system is 42382.8 J.